Effect of Acupressure at PC6 on Nausea and Vomiting During Pregnancy: a Randomized Controlled Trial - Melike Pündük Yılmaz; Saadet Yazıcı; İsmail Yılmaz (Medical Association of Pharmacopuncture Institute, 2023)
Background : Nausea and vomiting are among the most common medical problems during pregnancy, affecting 80% of mothers. Objectives: This study was conducted as a randomized controlled experimental study to determine the effect of acupressure applied by a wristband to the pericardium 6 (PC6) point on nausea and vomiting during pregnancy. Methods : The study population consisted of 74 pregnant women between 6-14 weeks of gestation who were experiencing nausea and vomiting. The study data was collected with personal information from the Pregnancy-Unique Quantification of Emesis Scale (PUQE). Experimental and control groups were selected by a simple random method. The experimental group wore acupressure wristbands for one week, while the control group did not use any method to alleviate nausea and vomiting. One week later, the PUQE scale was applied to both groups. Results : The acupressure wristbands decreased the nausea and vomiting scores of the pregnant women in the experimental group without statistical significance but did not change the nausea and vomiting scores of the pregnant women in the control group. Conclusion : Acupressure wristbands can be used to prevent nausea and vomiting during pregnancy.